Analysis Of The Economic Potential And Efficiency Of Cucurbitaceae Agricultural Businesses In The Peatlands - Syamsuri, Syamsuri (JURNAL AGRIBISAINS, 2024)
The purpose of this study was to analyze the economic potential of peatland utilization based on local wisdom by farmers in the Rasau Jaya Village and to analyze the most efficient Cucurbitaceae species to run based on the results of production BEP values, price BEP, ROI, PP, and R/C. The method used in this study is descriptive with a Participatory Rural Appraisal approach, meaning that it involves the active role of the community in obtaining data. Data collection techniques were carried out through observation and interviews using questionnaires. Sample collection was carried out by purposive sampling, with a total sample that met the inclusion criteria of 21 people. Analysis of economic potential data is carried out by calculating farmer receipts and income, while efficiency analysis is carried out by looking at the value of production BEP, price BEP, ROI, PP, and R/C. The results showed that the receipts for pumpkin, cucumber, watermelon, melon, squash and bitter gourd respectively were Rp. 2,375,000, Rp. 2,400,000, Rp. 2,800,000, Rp. 3,000,000, Rp. 2,400,000 and Rp. 2,400,000. Income received successively Rp. 275,000, Rp. 220,000, Rp. 700,000, Rp. 900,000, Rp. 300,000 and Rp. 300,000. Efficiency analysis shows that Cucurbitacea farming is efficient to run, and the most efficient type of Cucurbitacea is melon. Based on the research results, it can be concluded that the Cucurbitaceae agricultural business has economic potential and is efficient to run, especially the melon type.